In vitro antibacterial activity of self-etch bio-active dental adhesives after artificial aging - Gülbike Demirel; Müjde Eryılmaz; Hande Şeberol; Gürkan Gür (European Oral Research)
PurposeThe aims to evaluate the antibacterial effect of different bioactive component containing dental adhesives before and after artificial aging.Materials and MethodsTwo bio-active adhesives; Clearfil Protect Bond and FL Bond II, two non-bioactive adhesives, Clearfil SE Bond and Clearfil S3 Bond were used for this study. Antibacterial activities of the fresh and aged samples against Streptococcus mutans were investigated with Direct Contact Test. Data were analyzed with Kruskal Wallis and Mann Whitney U multiple comparison tests.ResultsFor fresh samples FL Bond II and Clearfil Protect Bond exhibit similar antibacterial effect but Clearfil Protect Bond showed significantly higher antibacterial effect after aging the samples (p < 0.05).ConclusionsThe incorporation of bio-active antibacterial components into adhesive systems may be considered as a fundamental component in inhibiting residual Streptococcus mutans when considering the antibacterial effect of fresh samples of bio-active adhesives.